MENINGKATKAN KEMAMPUAN MENYANYI LAGU DAERAH GORONTALO MENGGUNAKAN MEDIA AUDIOVISUAL DI KELAS III SDN 1 BATUDAA KABUPATEN GORONTALO - Latif, Nurjana; Mimy Astuty Pulukadang; Nurainun; La Ode Karlan; Wiwy Triyanty Pulukadang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the research problem: “Can the use of audiovisual media improve the ability of third-grade students at SDN 1 Batudaa, Gorontalo Regency, to sing Gorontalo regional songs?” The objective of this study is to enhance students’ singing ability of Gorontalo regional songs through the implementation of audiovisual media. This research employed a Classroom Action Research (CAR) design, utilizing data collection techniques such as observation, tests, and documentation. The research subjects consisted of 20 third-grade students at SDN 1 Batudaa, Gorontalo Regency. The findings indicate a progressive improvement in students’ singing ability across the research cycles. In Cycle I, Meeting I, only 3 out of 20 students (15%) achieved the expected level of singing competence. This increased to 7 students (35%) in Cycle I, Meeting II. Furthermore, in Cycle II, Meeting I, the number of students achieving the expected competence rose to 14 (70%), and in Cycle II, Meeting II, it reached 18 students (90%). These results demonstrate a significant improvement in students’ ability to sing Gorontalo regional songs. In conclusion, the use of audiovisual media in the learning process effectively enhances the singing ability of Gorontalo regional songs among third-grade students at SDN 1 Batudaa, Gorontalo Regency. The implementation of iterative learning cycles contributed to measurable improvements in student performance, indicating that audiovisual media can serve as an effective instructional tool in music education at the elementary level.